A review on optical properties and application of transparent ceramics - Ojo Jeremiah Akinribide; Gadifele Nicolene Mekgwe; Samuel Olukayode Akinwamide; Fehmi Gamaoun; Chamil Abeykoon; Oluwagbenga T. Johnson; Peter Apata Olubambi (Journal of Materials Research and Technology, 2022)
Advanced expertise and technologies have been devoted to producing high functional materials with a polycrystalline nature, which is transparent to visible light for various manufacturing applications. Materials with a good lattice structure can also be adopted in the manufacturing of transparent ceramics. Observations from the literature showed that oxide-based transparent ceramics had been successfully utilized, owing to their remarkable mechanical properties, chemical stability, and a wide range of flexible synthesis routes. Translucent zirconia (ZrO2) ceramics have drawn enormous attention from researchers in different fields due to their outstanding properties such as oxygen (O2) conductivity, mechanical behavior, functional properties, high level of toughness, and thermal conductivity. The Cubic and tetragonal crystal structure of zirconia can be applied for stabilizing Yttria (Y2O3) to enhance its optical performance and mechanical strength. Due to high chemical stability and high refractive index within the range of 2.2, transparent yttria-stabilized zirconia ceramic has been found useable in varying applications, including electromagnetic radiation, and camera lenses. The purity of starting materials and sintering techniques has been considered the proper production process for obtaining fully dense ceramics with less than 0.01% residual porosity for optical transparency. Scientists compared both conventional and modern processing techniques for transparent ceramic materials, the findings shows that modern processing techniques were better in morphological/mechanical properties. Consequently, the major drawbacks experienced during the consolidation processes can be attributed to the chemical impurity of sintering methods, the ceramic or the processing flexibility of the ceramic, sintering aids employed, and microstructural characteristics (e.g., porosity). In this review, an effort was made to summarize the advancement of transparent YSZ ceramics, focusing on applications and various consolidation technologies.